Vitamin D3 promotes white fat beige through IL-27/P38MAPK/PGC-1α pathway - Zhou, Yanqiu; Shu, Junfang; Zhao, Yueying; Wu, Xiaorong; He, Zhijun; Lyu, Xinzhe; Zhou, Yong; Ma, Ling (Frontiers in Nutrition, 2025)
BackgroundObesity is turning into a more critical problem for public health. Vitamin D3 (VD3) may be strongly linked to obesity.ObjectivesThe study aims to examine the influence of VD3 on IL-27 levels and the molecular mechanism by which VD3 affects white fat beige through the IL-27/P38MAPK/PGC-1α pathway.MethodsFirstly, a small sample population study was conducted to compare the disparities in serum 25(OH)D3 and IL-27 between individuals with obesity and healthy control groups. Secondly, twenty-four Wistar rats were separated into three groups: CON, HFD, and HFD + VD3 groups. Following 7 weeks of intervention, detection of biochemical indicators in serum by enzyme-linked immunosorbent assay (ELISA), mRNA, and protein expression of vitamin D receptor (VDR), IL-27R, P38MAPK, PGC-1α, and UCP-1 in inguinal adipose tissue by RT-qPCR and western blot. Finally, 3T3-L1 cells were induced into a hypertrophic adipose model, knock down IL-27 or PGC-1α using small interfering RNA, treated with 100 nM Calcitriol for 24 h, and divided into CON, PA, PA + 1,25(OH)2D3, PA + si IL-27, PA + si IL-27 + 1,25(OH)2D3, PA + si PGC-1α, and PA + si PGC-1α + 1,25(OH)2D3 groups. Detection of TC, TG, and IL-27 levels by ELISA, mRNA, and protein expression of VDR, IL-27R, P38MAPK, PGC-1α, UCP-1, and CD137 in cell supernatant by RT-qPCR and western blot.ResultsA correlation was identified between serum 25(OH)D3 and IL-27 in the population-based study. However, no statistically significant difference in serum 25(OH)D3 or IL-27 levels was observed between the observation group and the control group. After VD3 intervention, TC, TG, and the number of LDs were significantly reduced in both HFD rats and 3T3-L1 cells, and serum IL-6 and MCP-1 in HFD rats were decreased. Meanwhile, there was a significant increase in mRNA and protein expression for VDR, IL-27R, P38MAPK, and PGC-1α. The expressions of the UCP-1 protein and the CD137 mRNA dramatically increased. Knockdown of IL-27 eliminated the increasing effect of calcitriol on the expression of P38MAPK, PGC-1α, UCP-1, and CD137 in 3T3-L1 cells, and knockdown of PGC-1α eliminated the increasing effect of calcitriol on the expression of UCP-1 and CD137 in 3T3-L1 cells.ConclusionThe study shows that VD3 may promote white fat beige through the IL-27/P38MAPK/PGC-1α pathway.